Lietuvos istorijos (1940-1990) periodizacijos ir koncepcijos formavimasis išeivijos istorikų studijose - Jakubčionis, Algirdas (Lietuvos istorijos studijos, 1997)
The beginning of the formation of new conceptions and the beginning of periodization of Lithuanian history was in 1987. Lithuanian emigrant historians were the main influences of this process. The first ideas of new periodization were formulated by the historian Z. Ivinskis. In his publications, and in the works of other historians, M. Budreckis, Th. Remeikis, R. Misiūnas, and S. Suziedelis, the periodization of Lithuanian history from 1940-1990 was created. The first period, 1940-1941, was named as the period of Soviet occupation (15 June 1940 and the annexation on 3 August 1940). The essence of this period is the Sovietization of Lithuania and the genocide of the Lithuanian people. The second period, 1941-1944, was named as the period of Nazi occupation. During these years, the Lithuanian emigrant historians emphasized anti-Nazi resistance in the Lithuanian nation. The third period, 1944-1953, was the time of the second Soviet occupation or reoccupation. Guerilla movements were the main feature of this period. From the years of postwar Stalinism to 1956, the period of re-emergence of national culture (R. Misiūnas) or of the maintenance of national identity began (Th. Remeikis). This period came to an end in 1968. The main feature of the next period was the passive anti-Soviet movement and the Lithuania Catholic Church’s struggle for religious rights. The last period of modern Lithuanian history started in 1988, and it was named as the period of the Lithuanian Awakening.